A review of comprehension subskills: A Scientometrics perspective. (February 2020) - Aryadoust, Vahid
Abstract: Even though the field of applied linguistics has witnessed a growth of research in the areas of comprehension (listening and reading) subskills, there is currently no universally accepted taxonomy for categorizing them. Using a dataset of 192 publications, a document co-citation analysis was conducted. Eighteen discrete research clusters were identified, comprising 73 empirically investigated comprehension subskills, of which 55 were related to first language (L1) comprehension and 18 were associated with second language (L2) comprehension. Fifteen research clusters (83.33%) were focused on lower-order L1 processing abilities in reading such as orthographic processing and speeded word reading. The remaining three clusters were relatively small, and focused on L2 comprehension subskills. The list of subskills was visualized in the form of a codex that serves as the first integrative framework for empirically investigated comprehension subskills and processing abilities. The need for conducting experimental investigations to improve the understanding of L2 comprehension subskills was highlighted.